Role of Indra Vati in the management of Type II Diabetes mellitus (Madhumeha) - A Review Article - Suman, Deepak; Chakraborty, Sayantan; Kundu, Debasis (International Research Journal of Ayurveda & Yoga, 2020)
Diabetes is a disease of global concern. With increased modernisation and materialism its incidence is increasing day by day. This might be because of the adaptation of more sedentary lifestyle by the people. Diabetes mellitus is a disease in which there is either complete lack of insulin or there is resistance to the action of insulin disturbing the metabolism of carbohydrate, fats and proteins. According to Aetiological factor, pathogenesis and clinical features Diabetes mellitus correlated with Madhumeha in Ayurveda. Madhumeha is a type of Vataja Prameha in which patient passes honey like sweet urine (Raised level of sugar in urine & Hyperglycemia). It is one of the Santarpanottha Vyadhi. Guru, Snigdha, Pichhila Ahara, Pishtanna, excessive milk and milk products, lack of exercises are mentioned as the cause of Madhumeha. In today’s context excessive intake of all the fast food like pizza, burger etc which are Guru as well as made of refined wheat flour (Pishtanna), Paneer, cheese (milk products), and sweets made of jaggery or other substances comes under the Aharaj Nidana of Prameha/Madhumeha. Similarly, sedentary lifestyle comes under the Viharaja Nidana. Modern science also recognises these factors as a cause of diabetes mellitus. Though Type 2 DM was earlier common in middle aged population but nowadays even a younger group of people are found to have Type 2 DM. Due to wide spectrum of disease, lack of effective medicine, need of time is to go for cost effective, safe and efficient treatment of Madhumeha. Keeping all above points in mind the Indra vati has been selected to know the effect in treating Madhumeha (Diabetes Mellitus). Indra vati consists of 4 main contents, which are Rasa sindoora, Vanga Bhasma, Arjun and Shalmali.